PDMS / ferrocenyl MOF catalytic material coating liquid, PDMS / ferrocenyl MOF composite membrane as well as preparation method and application of PDMS / ferrocenyl MOF composite membrane
Through the use of PDMS/ferrocene-based MOF catalytic material coating solution and composite membrane, combined with membrane distillation and photocatalytic technology, the stability and recycling of phenolic substances in coal chemical wastewater were solved, and efficient degradation and recycling were achieved. Improves the chemical stability and industrial applicability of the materials.
Patent Information
- Application Number
- CN202411330093.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art in the coal chemical industry has poor stability and is difficult to recover, and it cannot effectively degrade phenolic substances in coal chemical wastewater, especially phenolic substances in dissolved oil, and the membrane separation method has high cost and poor chemical stability. , easy to blockage and other problems.
The coating solution and composite membrane of PDMS/ferrocene-based MOF catalytic material are used to improve the stability and recycling of MOF materials through PDMS coating, and combined with membrane distillation technology and photocatalytic action to achieve high efficiency on phenolic substances. degradation.
It realizes efficient degradation and recycling of phenolic substances in coal chemical wastewater, improves the chemical stability and recycling of materials, solves the cost and stability of membrane separation methods, and has high application in industrial applications. Sex and efficiency.
Smart Images

Figure CN119114158A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phenol-containing wastewater treatment, and is a PDMS / ferrocene-based MOF catalytic material coating liquid, a PDMS / ferrocene-based MOF composite membrane, and a preparation method and application thereof. Background Art
[0002] In recent years, the coal chemical industry has developed rapidly in Inner Mongolia, Shaanxi, Shanxi, Xinjiang and other places, and its development scale has also been increasing. As a result, a large amount of toxic and difficult-to-treat semi-coke wastewater has been produced. Semi-coke wastewater contains a large amount of difficult-to-degrade and highly toxic pollutants such as ammonia nitrogen, phenols, benzene series, polycyclic aromatic hydrocarbons and heterocyclic compounds. Among them, high oil content will not only block the equipment, but also seriously inhibit the activity of microorganisms in subsequent biochemical treatment, and deteriorate the treatment effect. Therefore, the removal of oil substances in semi-coke wastewater treatment is the first issue to be considered. The existence state of oil in water can be divided into floating oil, dispersed oil, emulsified oil, dissolved oil and some solids. Among them, the oil particle diameter of dissolved oil is the smallest, the content is the highest, and the properties are the most stable, and phenolic substances in dissolved oil account for the vast majority. At present, there are many methods for treating dissolved oil, such as flocculation, adsorption, ozone oxidation, Fenton oxidation, etc. At the same time, many corresponding functional materials have been developed to treat oil-water mixtures and phenolic substances in wastewater, but most materials cannot effectively separate oil substances from oil-water mixtures. Therefore, it is urgent to develop an ideal material with excellent separation performance, low cost and environmental friendliness to efficiently remove oil substances from oil-water mixtures. Membrane technology has the advantages of not requiring the addition of chemical agents, simple separation operation, low energy consumption in the separation process, and the ability to treat a large amount of wastewater in a short period of time. In the past decade, it has gradually become an important means of oil-water separation. However, membrane separation methods have problems such as expensive membrane components, large deformation under the influence of temperature, poor chemical stability, and easy clogging and contamination of the membrane, which need to be solved urgently.
[0003] Membrane distillation (MD) technology is a membrane separation technology that applies microporous hydrophobic membranes to membrane distillation devices. It has the advantages of high separation efficiency, low operating temperature, and low energy consumption. It has broad application prospects in the fields of seawater desalination, separation and concentration, and wastewater treatment. Traditional membrane distillation is made using polymers that have good hydrophobicity (such as PVDF, PTFE, PP, PES, and PE). Muhammad et al. {QASIM M, SAMAD IU, DARWISH NA, HILAL N. Comprehensive review of membrane design and synthesisfor membrane distillation [J]. Desalination, 2021, 518(115168).} listed the MD membranes currently available on the market, among which stretched PTFE and PE membranes and phase-inverted PVDF and PP membranes are the main ones. PTE, PET, and ceramic membranes are also used to prepare MD membranes. However, PVDF and ceramics are generally more expensive and expensive to manufacture, while MD membranes as engineering materials require cheaper membranes. Polydimethylsiloxane (PDMS) has SiO 2 It has the characteristics of safety, reliability, non-toxicity, pollution-free, non-corrosiveness, aging resistance and long service life. Because the side chain structure contains "organic groups", it has the characteristics of both organic and inorganic materials. It has strong hydrophobicity and can be used as a binder to connect components together to achieve the combination of low surface energy materials and substrates. It has excellent film-forming properties and shows great application potential in the preparation of MD membrane materials. Although membrane separation can separate and concentrate pollutants in water, it still faces the problem of subsequent decomposition and treatment of toxic chemicals. Therefore, designing a material that can effectively separate a large amount of organic pollutants in water and eliminate their environmental pollution through degradation is a direction worth exploring.
[0004] MOF (metal organic framework) materials have been gradually applied in the field of oil-water separation due to their low density, high porosity, high specific surface area, mild synthesis conditions, and easy-to-build and adjust microstructures and pore sizes. In recent years, it has also been found that MOF, as a semiconductor, has a large number of catalytic active sites, which makes it have great potential in the field of catalytic degradation of organic pollutants. UiO-66, synthesized from zirconium precursors and terephthalic acid, is considered to be an effective MOF catalyst with high specific surface area, excellent water stability, and adjustable pore size and optical properties. However, UiO-66 still has shortcomings, such as low electron-hole separation efficiency, incompatibility of pore size with small molecule pollutants, etc., which cannot achieve efficient adsorption, and most MOF materials exist in powder form, which is difficult to recycle from water bodies. Loading MOF on a carrier that is easy to recycle and improving chemical stability is of great significance for the practical application of materials. Currently, hydrophobic polydimethylsiloxane coating has been proven to be an effective way to improve the stability of MOF {WU P, JIANG M, LI Y, LIU Y, WANG J. Highlyefficient photocatalytic hydrogen production from pure water via aphotoactive metal–organic framework and its PDMS@MOF [J]. Journal of Materials Chemistry A, 2017, 5(17): 7833-7838.}.
[0005] Membrane distillation can concentrate pollutants in water, but it cannot handle the subsequent degradation of toxic chemicals. At the same time, MOF materials also have the problem of poor stability in water and difficulty in recycling. In addition, the current research on photocatalytic materials is mainly focused on the treatment of trace organic matter in water, and there is little research on their application in coal chemical wastewater with high organic pollutant content. Summary of the invention
[0006] The present invention provides a PDMS / ferrocene-based MOF catalytic material coating liquid, a PDMS / ferrocene-based MOF composite membrane, and a preparation method and application thereof, which overcome the deficiencies of the above-mentioned prior art and can effectively solve the problems in the existing coal chemical industry and industrial wastewater field that the treatment materials have poor stability and are difficult to recycle, and the treatment effect cannot meet the treatment needs of coal chemical wastewater.
[0007] One of the technical solutions of the present invention is achieved by the following measures: a method for preparing a PDMS / ferrocene-based MOF catalytic material coating liquid, wherein the PDMS / ferrocene-based MOF catalytic material coating liquid is composed of an agent A and an agent B; The preparation method of agent A is as follows: Dissolving a required amount of room temperature vulcanized methyl silicone rubber (RTV-107) and high hydrogen-containing silicone oil in a first solvent to obtain a reaction solution, adding a catalyst, and stirring to react to obtain agent A; The preparation method of Agent B is as follows: The ferrocene MOF powder is dispersed in the second solvent to obtain agent B.
[0008] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions: In the preparation method of the above-mentioned agent A, the hydrogen content of the high hydrogen silicone oil is 1.55% to 1.60%.
[0009] In the preparation method of the above-mentioned agent A, the reaction time is 1 h to 2 h, and the reaction temperature is 15°C to 35°C.
[0010] In the preparation method of the above-mentioned agent A, the catalyst is dibutyltin dilaurate (DY-12).
[0011] In the preparation method of the above-mentioned agent A, the first solvent is one of xylene, ethyl acetate or n-hexane.
[0012] In the preparation method of the above-mentioned agent A, in the reaction solution, the mass fraction of room temperature vulcanized methyl silicone rubber is 10% to 20%, the mass fraction of high hydrogen silicone oil is 0.15% to 0.35%, and the amount of catalyst is 0.15% to 0.35% of the total mass of the reaction solution.
[0013] In the preparation method of the above-mentioned agent B, the second solvent is ethyl acetate.
[0014] In the preparation method of the above-mentioned agent B, the ratio of ferrocene MOF powder to the second solvent is 10 g to 25 g of ferrocene MOF powder per 1 L of the second solvent.
[0015] In the preparation method of the above-mentioned agent B, the ferrocene MOF powder is prepared according to the following steps: 1,1'-Ferrocenylcarboxylic acid (H 2 FDC) and zirconium acetate (Zr(OAc) 4 ) is dissolved in N,N-dimethylformamide (DMF), mixed evenly, and a nucleating agent, glacial acetic acid, is added to obtain a black-brown ferrocene MOF precursor solution; the ferrocene MOF precursor solution is added to a reactor, and after reaction, the ferrocene MOF powder is obtained after washing and drying.
[0016] The volume ratio of agent A to agent B in the above PDMS / ferrocene-based MOF catalytic material coating liquid is 17.5:1 to 25:1.
[0017] The second technical solution of the present invention is achieved by the following measures: a PDMS / ferrocene-based MOF catalytic material coating liquid obtained according to the preparation method of one of the above technical solutions.
[0018] The third technical solution of the present invention is achieved by the following measures: A method for preparing a PDMS / ferrocene-based MOF composite membrane is carried out according to the following steps: The agent A and the agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid are mixed to obtain a mixed liquid, the mixed liquid is attached to the support layer, and the PDMS / ferrocene-based MOF composite membrane is obtained after curing.
[0019] The above-mentioned curing temperature is 50°C to 90°C, and the curing time is 30 min to 3 h.
[0020] The supporting layer is a porous film with a pore size of 0.4 μm to 0.6 μm.
[0021] The thickness of the cured layer of the PDMS / ferrocene-based MOF catalytic material coating liquid on the PDMS / ferrocene-based MOF composite membrane after curing is 15 μm to 25 μm.
[0022] The fourth technical solution of the present invention is achieved by the following measures: a PDMS / ferrocene-based MOF composite membrane prepared by a method for preparing a PDMS / ferrocene-based MOF composite membrane.
[0023] The fifth technical solution of the present invention is achieved through the following measures: application of a PDMS / ferrocene-based MOF composite membrane in the treatment of phenol-containing wastewater.
[0024] The present invention provides a method for preparing a PDMS / ferrocene-based MOF catalytic material coating liquid and a PDMS / ferrocene-based MOF composite membrane, and improves the stability of the MOF material by coating with PDMS, solves the problem that the MOF material is difficult to recycle, can effectively degrade phenolic substances in coal chemical wastewater, and is easy to recycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Attached Figure 1 This is the UV spectrum of phenol degradation by the PDMS / ferrocenyl MOF composite membrane prepared in Example 17 and Examples 21 to 23 of the present invention.
[0026] Attached Figure 2 SEM electron microscope images of the surface (left picture) and cross-section (right picture) of the PDMS / ferrocene-based MOF composite membrane provided in Example 21 of the present invention.
[0027] Attached Figure 3 This is the XPS spectrum of the ferrocenium-based MOF powder in Example 17 of the present invention. DETAILED DESCRIPTION
[0028] The present invention is not limited by the following embodiments, and the specific implementation method can be determined according to the technical scheme of the present invention and the actual situation. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all chemical reagents and chemicals known and used in the prior art; unless otherwise specified, the percentages in the present invention are all mass percentages; unless otherwise specified, the solutions in the present invention are all aqueous solutions with water as the solvent, for example, hydrochloric acid solution is a hydrochloric acid aqueous solution; the normal temperature and room temperature in the present invention generally refer to a temperature of 15°C to 25°C, and are generally defined as 25°C.
[0029] The present invention will be further described below in conjunction with embodiments: Example 1: A method for preparing the PDMS / ferrocene-based MOF catalytic material coating liquid, wherein the PDMS / ferrocene-based MOF catalytic material coating liquid is composed of agent A and agent B; The preparation method of agent A is as follows: Dissolving a required amount of room temperature vulcanized methyl silicone rubber (RTV-107) and high hydrogen-containing silicone oil in a first solvent to obtain a reaction solution, adding a catalyst, and stirring to react to obtain agent A; The preparation method of Agent B is as follows: The ferrocene MOF powder is dispersed in the second solvent to obtain agent B.
[0030] After the PDMS / ferrocene-based MOF catalytic material coating liquid of the present invention is cured, various forms of photocatalytic materials can be prepared, including but not limited to: photocatalytic degradation materials in the form of a thin film obtained by coating on a support layer, photocatalytic degradation materials in the form of particles formed by direct curing and crushing, photocatalytic degradation materials in the form of a thin film obtained by scraping the film after casting on a flat plate and directly curing, and photocatalytic degradation materials in the form of plate membranes, tubular membranes, roll membranes, hollow fiber membranes, etc. obtained by coating on different materials.
[0031] Example 3: As an optimization of the above example, in the preparation method of agent A, the hydrogen content of the high hydrogen silicone oil is 1.55% to 1.60%.
[0032] Example 4: As an optimization of the above example, in the preparation method of agent A, the reaction time is 1 h to 2 h, and the reaction temperature is 15°C to 35°C.
[0033] Example 5: As an optimization of the above example, in the preparation method of agent A, the catalyst is dibutyltin dilaurate (DY-12).
[0034] Example 6: As an optimization of the above example, in the preparation method of agent A, the first solvent is one of xylene, ethyl acetate or n-hexane.
[0035] Example 7: As an optimization of the above example, in the preparation method of Agent A, in the reaction solution, the mass fraction of room temperature vulcanized methyl silicone rubber is 10% to 20%, the mass fraction of high hydrogen silicone oil is 0.15% to 0.35%, and the amount of catalyst is 0.15% to 0.35% of the total mass of the reaction solution.
[0036] Example 8: As an optimization of the above example, in the preparation method of agent B, the second solvent is ethyl acetate.
[0037] Example 9: As an optimization of the above example, in the preparation method of agent B, the ratio of ferrocene MOF powder to the second solvent is 10 g to 25 g of ferrocene MOF powder per 1 L of the second solvent.
[0038] Example 10: As an optimization of the above example, in the preparation method of agent B, ferrocene MOF powder is prepared according to the following steps: 1,1'-Ferrocenylcarboxylic acid (H 2 FDC) and zirconium acetate (Zr(OAc) 4 ) is dissolved in N,N-dimethylformamide (DMF), mixed evenly, and a nucleating agent, glacial acetic acid, is added to obtain a black-brown ferrocene MOF precursor solution; the ferrocene MOF precursor solution is added to a reactor, and after reaction, the ferrocene MOF powder is obtained after washing and drying.
[0039] Specifically, the molar ratio of 1,1'-ferrocenylcarboxylic acid, zirconium acetate and glacial acetic acid is 1:1:50 to 1:1:150, the reaction temperature is 120° C. to 140° C., and the reaction time is 6 h to 9 h.
[0040] Example 11: As an optimization of the above example, the volume ratio of agent A to agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid is 17.5:1 to 25:1.
[0041] Example 12: The preparation method of the PDMS / ferrocene-based MOF composite membrane is carried out according to the following steps: The agent A and the agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid are mixed to obtain a mixed liquid, and the mixed liquid is attached to the support layer, and the PDMS / ferrocene-based MOF composite membrane is obtained after curing. The specific attachment method can be a known method such as dip coating and spray coating.
[0042] Example 13: As an optimization of the above example, the curing temperature is 50°C to 90°C, and the curing time is 30 min to 3 h.
[0043] Embodiment 14: As an optimization of the above embodiment, the support layer is a porous film with a pore size of 0.4 μm to 0.6 μm. The specific material of the support layer includes but is not limited to: nylon membrane, polyvinylidene fluoride membrane, ceramic membrane, mixed cellulose ester membrane, PP membrane, PE membrane, etc.
[0044] Example 15: As an optimization of the above example, the thickness of the solidified layer of the PDMS / ferrocene-based MOF catalytic material coating liquid on the PDMS / ferrocene-based MOF composite membrane after solidification is 15 μm to 25 μm.
[0045] Example 16: Application of the PDMS / ferrocene-based MOF composite membrane in the treatment of phenol-containing wastewater.
[0046] In practical applications, the PDMS / ferrocene-based MOF composite membrane of the present invention can be configured according to the size of the membrane distillation device, and combined with potassium persulfate to catalytically degrade organic pollutants in phenol-containing wastewater under the action of visible light.
[0047] Embodiment 17: (I) Preparation of PDMS / ferrocene-based MOF catalytic material coating liquid: Take the required amount of 1.0 g RTV-107 and 0.035 g high hydrogen silicone oil and dissolve them in 8.75 g n-hexane, stir and disperse, add 0.035 g catalyst DY-12, stir and react at room temperature for 1.5 h to obtain agent A; 54.8 mg H 2 FDC and 64.5 mg Zr(OAc) 4 Dissolve in 6 mL DMF, mix evenly with ultrasonic, add 1.2 g glacial acetic acid, stir evenly, add to the reactor, and react at 130 °C for 7 h; after cooling to room temperature, the precipitate is washed with methanol and centrifuged three times, and dried at 80 °C for 3 h to obtain brown ferrocenyl MOF powder; then disperse 10 mg ferrocenyl MOF powder in 0.4 mL ethyl acetate, disperse evenly with ultrasonic to obtain agent B.
[0048] (II) Preparation of PDMS / ferrocene-based MOF composite membrane: Agent A and agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid were mixed uniformly in a volume ratio of 17.5:1 to obtain a mixed liquid, the mixed liquid was attached to a nylon membrane, and cured at 60° C. for 0.5 h to obtain a PDMS / ferrocene-based MOF composite membrane.
[0049] Embodiment 18: (I) Preparation of PDMS / ferrocene-based MOF catalytic material coating liquid: Take the required amount of 12.5 g RTV-107 and 0.03 g high hydrogen silicone oil and dissolve them in 8.0 g n-hexane, stir and disperse, add 0.03 g catalyst DY-12, stir and react at room temperature for 1.5 h to obtain agent A; 54.8 mg H 2 FDC and 64.5 mg Zr(OAc) 4 Dissolve in 6 mL DMF, mix evenly with ultrasonic, add 0.6 g glacial acetic acid, stir evenly, add to the reactor, and react at 120°C for 9 h; after cooling to room temperature, the precipitate is washed with methanol and centrifuged three times, and dried at 80°C for 3 h to obtain brown ferrocenyl MOF powder; then disperse 10 mg ferrocenyl MOF powder in 0.4 mL ethyl acetate, disperse evenly with ultrasonic to obtain agent B.
[0050] (II) Preparation of PDMS / ferrocene-based MOF composite membrane: Agent A and agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid were mixed evenly in a volume ratio of 20:1 to obtain a mixed liquid, the mixed liquid was attached to a nylon membrane, and cured at 60°C for 1.0 h to obtain a PDMS / ferrocene-based MOF composite membrane.
[0051] Embodiment 19: (I) Preparation of PDMS / ferrocene-based MOF catalytic material coating liquid: Take the required amount of 1.75 g RTV-107 and 0.025 g high hydrogen silicone oil and dissolve them in 8.75 g n-hexane, stir and disperse, add 0.025 g of catalyst DY-12, stir and react at room temperature for 1.5 h to obtain agent A; 54.8 mg H 2 FDC and 64.5 mg Zr(OAc) 4 Dissolve in 6 mL DMF, mix evenly with ultrasonic wave, add 0.9 g glacial acetic acid, stir evenly, add into the reactor, and react at 140 °C for 6 h; after cooling to room temperature, the precipitate is washed with methanol and centrifuged three times, and dried at 80 °C for 3 h to obtain brown ferrocenyl MOF powder; then disperse 10 mg ferrocenyl MOF powder in 0.4 mL ethyl acetate, disperse evenly with ultrasonic wave, and obtain agent B.
[0052] (II) Preparation of PDMS / ferrocene-based MOF composite membrane: Agent A and agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid were mixed uniformly in a volume ratio of 22.5:1 to obtain a mixed liquid, the mixed liquid was attached to a nylon membrane, and cured at 60°C for 2.0 h to obtain a PDMS / ferrocene-based MOF composite membrane.
[0053] Embodiment 20: (I) Preparation of PDMS / ferrocene-based MOF catalytic material coating liquid: Take the required amount of 2.0 g RTV-107 and 0.015 g high hydrogen silicone oil and dissolve them in 8.0 g n-hexane, stir and disperse, add 0.015 g catalyst DY-12, stir and react at room temperature for 1.5 h to obtain agent A; 54.8 mg H 2 FDC and 64.5 mg Zr(OAc) 4 Dissolve in 6 mL DMF, mix evenly with ultrasonic, add 1.5 g glacial acetic acid, stir evenly, add to the reactor, and react at 130 °C for 8 h; after cooling to room temperature, the precipitate is washed with methanol and centrifuged three times, and dried at 80 °C for 3 h to obtain brown ferrocenyl MOF powder; then disperse 10 mg ferrocenyl MOF powder in 0.4 mL ethyl acetate, disperse evenly with ultrasonic to obtain agent B.
[0054] (II) Preparation of PDMS / ferrocene-based MOF composite membrane: Agent A and agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid were mixed evenly in a volume ratio of 25:1 to obtain a mixed liquid, the mixed liquid was attached to a nylon membrane, and cured at 60°C for 3.0 h to obtain a PDMS / ferrocene-based MOF composite membrane.
[0055] Example 21: The only difference from Example 17 is that the volume ratio of agent A to agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid is 20:1.
[0056] Example 22: The only difference from Example 17 is that the volume ratio of agent A to agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid is 22.5:1.
[0057] Example 23: The only difference from Example 17 is that the volume ratio of agent A to agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid is 25:1.
[0058] Comparative Example 1: The only difference from Example 17 is that the volume ratio of agent A to agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid is 15:1.
[0059] Comparative Example 2: The preparation process of the PDMS membrane without adding ferrocene-based MOF is as follows: take the required amount of 1.75 g RTV-107 and 0.025 g high hydrogen silicone oil, dissolve them in 8.25 g n-hexane, stir and disperse, add 0.025 g of catalyst DY-12, stir and react at room temperature for 1.5 h to obtain a coating liquid, apply the coating liquid on a nylon membrane, and cure it at 60°C for 0.5 h to obtain a PDMS membrane.
[0060] Comparative Example 3: Ferrocene-based MOF powder without PDMS added, the preparation process is as follows: 54.8 mg H 2 FDC and 65.4 mg Zr(OAc) 4 Dissolve in 6 mL DMF, mix evenly with ultrasound, add 1.2 g glacial acetic acid, stir evenly, add to the reactor, and react at 130 °C for 7 h; after cooling to room temperature, the precipitate is washed with methanol and centrifuged three times, and dried at 80 °C for 3 h to obtain brown ferrocene-based MOF powder.
[0061] Phenol is the most common pollutant in semi-coal wastewater, and phenol solution is the most representative simulated coal chemical wastewater. It is generally recognized to evaluate the ability of membranes to intercept and treat organic matter. The UV spectra of the PDMS / ferrocene-based MOF composite membranes prepared in Examples 17 and 21 to 23 for degradation of phenol (phenol solution concentration 50 mg / L) are shown in Figure 1. Figure 1 ( Figure 1 In the figure, a is Example 17, b is Example 21, c is Example 22, and d is Example 23), wherein the Initial curve is the initial ultraviolet absorption spectrum of the feed solution (phenol solution), the Feed (Light 0.5 h) curve is the ultraviolet absorption spectrum of the feed solution after 0.5 h of photocatalysis, the Feed curve is the ultraviolet absorption spectrum of the feed solution at the end of the reaction, and the Distillate curve is the ultraviolet absorption spectrum of the distillate after membrane distillation and photocatalysis. By comparing the absorbance at the maximum absorption peak of the Initial curve and the Feed curve, it can be seen that the PDMS / ferrocene-based MOF composite membrane of the present invention can effectively catalyze the degradation of phenol in the feed liquid, achieving the goal of catalyzing the degradation of concentrated and difficult-to-treat phenol in the feed liquid while purifying water through membrane distillation, solving the problem that membrane distillation cannot handle the subsequent degradation of toxic chemicals; by comparing the absorbance at the maximum absorption peak of the Feed and Distillate, i.e. the feed liquid and the distillate, it can be seen that the PDMS / ferrocene-based MOF composite membrane of the present invention can effectively intercept phenol in the feed liquid, achieving the goal of concentrating the concentration of pollutants in the water. At the same time, the continuous degradation of phenol in the feed liquid also improves the efficiency of membrane separation, making the composite membrane have great potential in treating wastewater containing high concentrations of pollutants. Figure 2 The surface (left) and cross-section (right) SEM images of the PDMS / ferrocene-based MOF composite membrane provided in Example 21. Figure 2 It can be seen that PDMS is firmly loaded on the support layer. From the SEM electron microscope image of the composite membrane surface, it can be seen that there are many irregular small holes distributed on the surface of the membrane; from the SEM electron microscope image of the cross section of the composite membrane, it can be seen that the PDMS layer is about 20 μm and penetrates into the support layer, reducing the pore size of the support layer to achieve the micropore size required for membrane distillation.
[0062] Attached Figure 3 is the XPS spectrum of the ferrocenyl MOF powder in Example 17. Figure 3 The elemental composition of ferrocene-based MOF can be known, among which the peaks at 284.80 eV, 286.10 eV and 288.45 eV correspond to CC, COC and OC=O bonds, respectively; the peaks at 529.1 eV and 30.3 eV are related to lattice oxygen and surface adsorbed oxygen; the peaks at 707.78 eV and 720.38 eV are related to Fe in ferrocene. 2+ The binding energies at 182.08 eV and 184.48 eV are consistent with the Zr-O bond, indicating that Zr 6 O 8 Clusters act as nodes in TFMOF.
[0063] PDMS / ferrocene-based MOF membrane organic matter treatment performance test: The present invention uses phenol solution and coal chemical wastewater as test solutions to test the photocatalytic degradation performance of phenols in simulated wastewater and coal chemical wastewater on the PDMS / ferrocene-based MOF membranes prepared in Examples 17 and Examples 21 to 23 and the water treatment materials of Comparative Examples 1 to 3. The concentration of the phenol solution in the simulated wastewater is 50 mg / L, the content of phenols in the coal chemical wastewater is 670 mg / L, and the initial COD is 2370 mg / L.
[0064] The PDMS / ferrocene-based MOF membranes of Examples 17, Examples 21 to 23, and the membrane materials of Comparative Examples 1 and 2 used in the test are all 5 cm diameter discs, and the thickness of the solidified layer is about 20 μm. The specific operation is: 0.75 g / L of potassium persulfate is added to the feed liquid and then added to the membrane distillation device through the injection port, and then the membrane material is fixed on the membrane distillation device, and a 300 W 420 nm xenon lamp is used to irradiate the side of the membrane material in contact with the feed liquid, and the vacuum degree of the side of the membrane in contact with the air is maintained at 0.09 MPa, and the distillate is collected by cooling and condensing. The test of Comparative Example 3 is: without using a membrane distillation device, the ferrocene-based MOF powder without PDMS is directly put into the feed liquid, and the amount of ferrocene-based MOF powder is 0.75 g / L. The test results are shown in Table 1.
[0065] As can be seen from Table 1, the addition of the PDMS / ferrocene-based MOF membrane of the present invention has a higher degree of improvement in the removal rate of phenol and the removal rate of volatile phenols and COD of actual coal chemical wastewater compared to the PDMS membrane without adding ferrocene-based MOF in Comparative Example 2. In the PDMS / ferrocene-based MOF membrane, when the value of agent A: agent B is too low, the permeation flux of the membrane will be increased, so that more organic pollutants pass through the composite membrane through the channel formed by ferrocene MOF, thereby reducing the interception performance of organic pollutants in water. Moreover, compared to the ferrocene-based MOF powder without adding PDMS in Comparative Example 3, the composite membrane has a significant improvement in the organic degradation of actual coal chemical wastewater. There are many organic and inorganic ions and solid particles in the wastewater that affect the catalytic degradation of MOF, which will fill the micropores on the surface of MOF, reduce the contact area between MOF and organic matter, thereby weakening the catalytic efficiency of MOF, and even causing MOF deactivation, and PDMS coated MOF powder can reduce the generation of the above problems.
[0066] The present invention has the following advantages: The preparation method is simple. The preparation method of the ferrocene-based MOF nanoparticles (agent B) and the PDMS prepolymer solution (agent A) with photocatalytic properties is simple, and a dense and uniform membrane distillation material can be obtained after simple blending and curing.
[0067] Compared with the Fenton technology, the PDMS / ferrocene-based MOF composite membrane combined with potassium persulfate oxidation technology of the present invention has a wider application range, higher selectivity, milder reaction, and uses H 2 FDC replaces the dibasic acid used in the traditional preparation of UiO-66 and UiO-67. The introduced iron element can effectively activate potassium persulfate and improve the catalytic efficiency of MOF materials.
[0068] The PDMS / ferrocene-based MOF composite membrane of the present invention combines the advantages of membrane distillation and MOF to achieve membrane separation and photocatalytic synergistic treatment of organic pollutants in water, with better treatment effect.
[0069] In summary, the present invention provides a PDMS / ferrocene-based MOF catalytic material coating liquid, including a PDMS prepolymer liquid (agent A) and ferrocene-based MOF nanoparticles with photocatalytic properties (agent B). The PDMS / ferrocene-based MOF composite membrane prepared by the coating liquid effectively utilizes the strong hydrophobicity of PDMS and the photocatalytic property of MOF to prepare a microporous hydrophobic membrane to synergistically treat a large number of organic pollutants that are difficult to treat in water, and shows a good treatment effect on phenolic pollutants. The PDMS / ferrocene-based MOF catalytic material coating liquid and the PDMS / ferrocene-based MOF membrane preparation method of the present invention have low energy consumption, short time consumption, simple preparation method, and the prepared membrane is dense and uniform, the membrane thickness can be adjusted, and it is easy to realize industrial production.
[0070] The above technical features respectively constitute various embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.
Claims
1. A method for preparing a PDMS / ferrocene-based MOF catalytic material coating liquid, characterized in that The PDMS / ferrocene-based MOF catalytic material coating liquid is composed of agent A and agent B; The preparation method of agent A is as follows: Dissolving a required amount of room temperature vulcanized methyl silicone rubber and high hydrogen content silicone oil in a first solvent to obtain a reaction solution, adding a catalyst, and stirring to react to obtain agent A; The preparation method of Agent B is as follows: The ferrocene MOF powder is dispersed in the second solvent to obtain agent B.
2. The method for preparing the PDMS / ferrocene-based MOF catalytic material coating liquid according to claim 1, characterized in that In the preparation method of agent A, the hydrogen content of the high hydrogen silicone oil is 1.55% to 1.60%; or / and, the reaction time is 1 h to 2 h, and the reaction temperature is 15°C to 35°C; or / and, the catalyst is dibutyltin dilaurate; or / and, the first solvent is one of xylene, ethyl acetate or n-hexane; or / and, in the reaction solution, the mass fraction of room temperature vulcanized methyl silicone rubber is 10% to 20%, the mass fraction of the high hydrogen silicone oil is 0.15% to 0.35%, and the amount of the catalyst is 0.15% to 0.35% of the total mass of the reaction solution.
3. The method for preparing the PDMS / ferrocenyl MOF catalytic material coating liquid according to claim 1 or 2, characterized in that In the preparation method of agent B, the second solvent is ethyl acetate; or / and, the ratio of ferrocene MOF powder to the second solvent is 10 g to 25 g of ferrocene MOF powder per 1 L of the second solvent; or / and, the ferrocene MOF powder is prepared according to the following steps: 1,1'-ferrocenecarboxylic acid and zirconium acetate are dissolved in N,N-dimethylformamide, mixed evenly, and a nucleating agent glacial acetic acid is added to obtain a black-brown ferrocene MOF precursor solution; the ferrocene MOF precursor solution is added to a reactor, and after the reaction, the ferrocene MOF powder is washed and dried to obtain the ferrocene MOF powder.
4. The method for preparing the PDMS / ferrocenyl MOF catalytic material coating liquid according to any one of claims 1 to 3, characterized in that The volume ratio of agent A to agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid is 17.5:1 to 25:
1.
5. A PDMS / ferrocene-based MOF catalytic material coating liquid obtained according to the preparation method of the PDMS / ferrocene-based MOF catalytic material coating liquid according to any one of claims 1 to 4.
6. A method for preparing a PDMS / ferrocene-based MOF composite membrane of the PDMS / ferrocene-based MOF catalytic material coating liquid according to claim 5, characterized in that Follow these steps: The agent A and the agent B in the PDMS / ferrocene-based MOF catalytic material coating liquid are mixed to obtain a mixed liquid, the mixed liquid is attached to the support layer, and the PDMS / ferrocene-based MOF composite membrane is obtained after curing.
7. The method for preparing a PDMS / ferrocene-based MOF composite membrane according to claim 6, characterized in that The curing temperature is 50°C to 90°C, and the curing time is 30 min to 3 h.
8. The method for preparing a PDMS / ferrocene-based MOF composite membrane according to claim 6 or 7, characterized in that The supporting layer is a porous film with a pore size of 0.4 μm to 0.6 μm; or / and, the thickness of the solidified layer after the PDMS / ferrocene-based MOF catalytic material coating liquid on the PDMS / ferrocene-based MOF composite membrane is solidified is 15 μm to 25 μm.
9. A PDMS / ferrocene-based MOF composite membrane prepared according to the method for preparing a PDMS / ferrocene-based MOF composite membrane according to any one of claims 6 to 8.
10. Use of the PDMS / ferrocenyl MOF composite membrane according to claim 9 in the treatment of phenol-containing wastewater.
